Psikoterapi dalam Menangani Enuresis Pada Anak Sekolah dengan Gangguan Cemas: Laporan Kasus - Wulan, Made Citra Riesti; Rahayu, Wayan Saka; Wayan Wiradana (International Journal Labs, 2025)
Enuresis is a condition of not being able to control urination or unconsciously urinating during the day or at night while asleep1. Secondary enuresis occurs in children who previously experienced a dry period of more than 6 months2. Primary enuresis occurs in children who do not experience any dry periods at all since birth. There is a relationship between mental disorders and enuresis, where as many as 20% of children with enuresis experience mental disorders such as social anxiety disorders and anxiety disorders5 Case: An 11-year-old girl, in grade 5 elementary school, was escorted by her mother to a psychiatric polyclinic because she complained since childhood that she continued to wet her bed every night. The patient admitted that every night he was afraid of sleeping alone. The patient also admitted that at school he was embarrassed to hang out with friends. Then given counseling, the patient is asked to start recording on the calendar. Installation of alarms. Patients are educated to reduce afternoon drinking before bedtime, trying to urinate before going to bed. The patient then came back to control 1 month later, the frequency of wetting was reduced only with psychotherapy. The fear of sleeping alone and missing class has decreased. Discussion: Enuresis is often accompanied by mental disorders such as anxiety disorders or depression. Psychotherapy can be given to look for anxiety and depressive factors, alarm therapy suggestions, optimal urinary practices, fluid intake, and positive reinforcement. The success of psychotherapy is almost 60% to 80%. Desmopressin is a first-line therapy to overcome enuresis. Conclusion: In the case of an elementary school girl who complained of always wetting her bed at night. Treatment is given psychotherapy. A study showed a defined success rate of 14 consecutive nights without wetting.